Isolation Of The Nucleotide-Binding Site Family Of Resistance - Artinano, Juan Carlos Cordero (Kansas State University, 1997)
Research findings over the past decade revealed exciting information regarding disease and pest resistance in plants. Scientists found that homology exists between genes (R genes) of different plant species that confer strain-specific resistance against a wide range of pathogens and pests including: viruses, bacteria, fungi, nematodes and insects. These genes have been found to be a strong, naturally occurring source of resistance in plants with great potential for environmentally safe applications in crop protection. The purpose of this study was to investigate the existence and expression of R genes in alfalfa (Medicago sativa L.) and to analyze the diversity in alfalfa and in the genus Medicago. We used a PCR approach with degenerate primers designed from the highly conserved motifs, P-Loop and GLPL, found within the nucleotide binding site (NBS) of NBS-LRR resistance genes. The degenerate PCR approach was used successfully on genomic DNA and cDNA from Medicago sativa and genomic DNA from thirteen other Medicago species. Sequence data from ninety-four clones of the NBS PCR product provided 51 Medicago sativa resistance gene analogs (MSRGA's) sharing from 35% to 99% homology. The eighteen families that share less than 95% homology represent the 51 MSRGA's. Additionally, dendrogram and bootstrap analysis showed that the 51 MSRGA's grouped in six major clusters that suggested three different evolutionary origins. Transcription of three of the MSRGA families was confirmed by RT-PCR. Diversity in resistance gene analogs between species of the genus Medicago was confirmed by restriction pattern analysis of the degenerate PCR products. The characterization of the MSRGA family in alfalfa and the diversity of resistance gene analogs in the genus Medicago provided by this study represent a pool of candidate resistance genes which will be fundamental for the development of disease and pest resistant alfalfa cultivars in the future.